For quality, equitable and inclusive education: sustainability in the transversal teaching of Civic Education - Capobianco, Rosaria (Formazione & insegnamento, 2021)
Education in sustainability is an urgent goal, which requires everyone, without distinction, to be aware of behaviors and lifestyles based on respect, on the ethics of responsibility, both towards people and towards the environment. Through the transversal teaching of civic education introduced by Law 92/2019, the school can educate current generations in the ethics of responsibility and sustainability. The structuring of a civic education curriculum developed by the teachers of the I.C. “Don Diana” of Casal di Principe offers the starting point for a reflection on respect and protection of the common good that passes through the logic of sustainable development.